Dirigiu-se para a sede social da Elite Flor da Liberdade e ofereceu um banquete aos visitantes: sobre a variação de proposições em complementos verbais - Berlinck, Rosane de Andrade [UNESP] (My University, 2011)
This study analyses the variable use of prepositions (particularly a and para) as verb complement in newspaper articles published in the early decades of the 20th century in São Paulo newspapers. The purpose is to investigate such variation in a moment that lies half way between a stage of almost complete dominance of the preposition a (the first half of the 19th century) and the appearance of preposition para, which would become the dominant variant in the end of the 20th century). Two main aspects are taken into account in the analysis: (i) semantic factors, associated with the verb and its complement and (ii) the genre in which the construction occurs (editorials, advertisements, social notes, news). D a t a a n a lysis fo l l ows t h e t h e o r e ti c a lmethodological proposal of the T heory of Language Variation and Change (Weinreich, Labov, Herzog, 1918, Labov, 1972, 1994, 2001) and adopts the concept of genre, as established in Bakhtin (1979). Other developments and current applications (Bazerman, 2005; Fiorin, 2006; Marcuschi, 2008), as well as discussions on gender in newspapers, as present in the work of Bonini (2003) and studies in the area of Communication are also taken into account. The results show a mixed picture including contexts effectively variable (which express a physical concrete movement, towards a goal that denotes a specific place) and contexts almost impermeable to the innovative variant (complements that show a human referent, predicators of verbal or perceptual transfer).

O presente estudo focaliza a variação no uso de preposições em contextos de complementação verbal em textos jornalísticos publicados nas primeiras décadas do século XX em jornais paulistas. O objetivo principal é caracterizar tal variação em um momento que se situa a meio caminho entre um estágio de predomínio quase absoluto da preposição a (primeira metade do século XIX ) e um quadro em que se destaca a preposição para como a variante dominante (fim do século XX ). Dois aspectos principais são levados em conta na análise: (i) fatores de natureza semântica, associados ao verbo e ao complemento e (ii) o gênero textual em que a construção ocorre (editorial, anúncio, nota social, notícia). A análise de dados segue a proposta teórico metodológicada Teoria da Variação e Mudança Linguísticas (Weinreich, Labov, Herzog, 1968; Labov,1972, 1994, 2001) e adota a concepção de gênero textual, tal como estabelecida a partir de Bakhtin (1979) e outros desdobramentos e aplicações atuais (Bazerman, 2005; Fiorin, 2006; Marcuschi 2008), além das discussões sobre gêneros nos jornais, presentes no trabalho de Bonini (2003) e em estudos da área de Comunicação. Os resultados revelam um quadro heterogêneo que inclui contextos efetivamente variáveis (em que se expressa um movimento físico, concreto, em direção de uma meta que denota um lugar concreto) e contextos quase impermeáveis à variante inovadora (complementos que denotam um referente humano e predicadores de transferência verbal /perceptual).
Keywords: Preposition; Verbal complementation; Genre; Linguistic variation; Brazilian Portuguese; Preposição; Complementação verbal; Gênero textual; Variação linguística; Português brasileiro